Consistency check between XML schema and class diagram for document versioning - Ibrahim, Rosziati; Aman, Hannani; Nayak, Richi; Jamel, Sapiee (Insight - Indonesian Society for Knowledge and Human Development, 2018)
A consistency check between design and implementation is usually done in order to check the correctness of the system’ requirements. However, if the requirements are changed over time, then the document versioning occurred within the requirements. For XML Schema, document versioning exists when there is a change in the XML Schema from its previous Schema. In order to detect the versioning of both XML Schemas, consistency rules check need to be performed to both class diagrams produced by both Schemas. The consistency between two XML Schemas are checked based on transformation rules and versioning rules. Transformation rules are used for translating the XML Schema into class diagram and versioning rules are used for checking the existing of document changes between two XML Schemas. Once two XML Schemas are different the consistency rules will be used for the consistency check. This paper presents an approach based on transformation rules and versioning rules to check consistency between XML Schema and UML class diagram when document versioning exist. The approach is then used for the case study to show how the consistency is checked in order to detect the versioning of two different XML Schemas. Based on the case study, the approach shows that two XML Schemas can be checked for their consistency when document versioning exist.